Biomimetic surface structures in steel fabricated with femtosecond laser pulses: influence of laser rescanning on morphology and wettability - Florian Baron, Camilo; Mimidis, Alexandros; Puerto, Daniel; Skoulas, Evangelos; Stratakis, Emmanuel; Solis, Javier; Siegel, Jan (Beilstein Journal of Nanotechnology, 2018)
The replication of complex structures found in nature represents an enormous challenge even for advanced fabrication techniques, such as laser processing. For certain applications, not only the surface topography needs to be mimicked, but often also a specific function of the structure. An alternative approach to laser direct writing of complex structures is the generation of laser-induced periodic surface structures (LIPSS), which is based on directed self-organization of the material and allows fabrication of specific micro- and nanostructures over extended areas. In this work, we exploit this approach to fabricate complex biomimetic structures on the surface of steel 1.7131 formed upon irradiation with high repetition rate femtosecond laser pulses. In particular, the fabricated structures show similarities to the skin of certain reptiles and integument of insects. Different irradiation parameters are investigated to produce the desired structures, including laser repetition rate and laser fluence, paying special attention to the influence of the number of times the same area is rescanned with the laser. The latter parameter is identified to be crucial for controlling the morphology and size of specific structures. As an example for the functionality of the structures, we have chosen the surface wettability and studied its dependence on the laser processing parameters. Contact angle measurements of water drops placed on the surface reveal that a wide range of angles can be accessed by selecting the appropriate irradiation parameters, highlighting also here the prominent role of the number of scans.
Keywords: biomimetics; femtosecond laser irradiation; laser-induced periodic surface structures; laser rescanning; steel; wettability

(untitled) - Bhushan, B.; Jung, Y. C.; Niemietz, A.; Koch, K. (Langmuir, 2009)

(untitled) - Stark, A. Y.; Badge, I.; Wucinich, N. A.; Sullivan, T. W.; Niewiarowski, P. H.; Dhinojwala, A. (Proc. Natl. Acad. Sci. U. S. A., 2013)

(untitled) - Vukusic, P.; Sambles, R.; Lawrence, C.; Wakely, G. (Appl. Opt., 2001)

(untitled) - Müller, F.; Kunz, C.; Gräf, S. (Materials, 2016)

(untitled) - Dorrer, C.; Rühe, J. (Beilstein J. Nanotechnol., 2011)

(untitled) - Hermens, U.; Kirner, S. V.; Emonts, C.; Comanns, P.; Skoulas, E.; Mimidis, A.; Mescheder, H.; Winands, K.; Krüger, J.; Stratakis, E.; Bonse, J. (Appl. Surf. Sci., 2017)

(untitled) - Liu, M.-N.; Wang, L.; Yu, Y.-H.; Li, A.-W. (Opt. Mater. Express, 2017)

(untitled) - Vorobyev, A. Y.; Guo, C. (J. Appl. Phys., 2015)

(untitled) - Gregorčič, P.; Šetina-Batič, B.; Hočevar, M. (Appl. Phys. A: Mater. Sci. Process., 2017)

(untitled) - Zorba, V.; Stratakis, E.; Barberoglou, M.; Spanakis, E.; Tzanetakis, P.; Anastasiadis, S. H.; Fotakis, C. (Adv. Mater., 2008)

(untitled) - Birnbaum, M. (J. Appl. Phys., 1965)

(untitled) - Vorobyev, A. Y.; Guo, C. (Laser Photonics Rev., 2013)

(untitled) - Puerto, D.; Garcia-Lechuga, M.; Hernandez-Rueda, J.; Garcia-Leis, A.; Sanchez-Cortes, S.; Solis, J.; Siegel, J. (Nanotechnology, 2016)

(untitled) - Bonse, J.; Hohm, S.; Kirner, S. V.; Rosenfeld, A.; Kruger, J. (IEEE J. Sel. Top. Quantum Electron., 2017)

(untitled) - Huang, M.; Zhao, F.; Cheng, Y.; Xu, N.; Xu, Z. (ACS Nano, 2009)

(untitled) - Bonse, J.; Rosenfeld, A.; Krüger, J. (J. Appl. Phys., 2009)

(untitled) - Bonse, J.; Höhm, S.; Rosenfeld, A.; Krüger, J. (Appl. Phys. A: Mater. Sci. Process., 2013)

(untitled) - Fuentes-Edfuf, Y.; Garcia-Lechuga, M.; Puerto, D.; Florian, C.; Garcia-Leis, A.; Sanchez-Cortes, S.; Solis, J.; Siegel, J. (Appl. Phys. Lett., 2017)

(untitled) - Tsibidis, G. D.; Fotakis, C.; Stratakis, E. (Phys. Rev. B, 2015)

(untitled) - Tsibidis, G. D.; Mimidis, A.; Skoulas, E.; Kirner, S. V.; Krüger, J.; Bonse, J.; Stratakis, E. (Appl. Phys. A: Mater. Sci. Process., 2018)

(untitled) - Ruiz de la Cruz, A.; Lahoz, R.; Siegel, J.; de la Fuente, G. F.; Solis, J. (Opt. Lett., 2014)

(untitled) - Gnilitskyi, I.; Gruzdev, V.; Bulgakova, N. M.; Mocek, T.; Orazi, L. (Appl. Phys. Lett., 2016)

(untitled) - Kirner, S. V.; Hermens, U.; Mimidis, A.; Skoulas, E.; Florian, C.; Hischen, F.; Plamadeala, C.; Baumgartner, W.; Winands, K.; Mescheder, H.; Krüger, J.; Solis, J.; et al. (Appl. Phys. A: Mater. Sci. Process., 2017)

(untitled) - Chen, T.; Liu, H.; Yang, H.; Yan, W.; Zhu, W.; Liu, H. (RSC Adv., 2016)

(untitled) - Kam, D. H.; Bhattacharya, S.; Mazumder, J. (J. Micromech. Microeng., 2012)

(untitled) - Ling, E. J. Y.; Saïd, J.; Brodusch, N.; Gauvin, R.; Servio, P.; Kietzig, A.-M. (Appl. Surf. Sci., 2015)

(untitled) - Zuhlke, C. A.; Anderson, T. P.; Alexander, D. R. (Appl. Surf. Sci., 2013)

(untitled) - Tanvir Ahmmed, K. M.; Grambow, C.; Kietzig, A.-M. (Micromachines, 2014)

Image released on the Report. Project LiNaBioFluid Deliverable 2.2: SEM images of nanostructures (2016)

(untitled) - Comanns, P.; Effertz, C.; Hischen, F.; Staudt, K.; Böhme, W.; Baumgartner, W. (Beilstein J. Nanotechnol., 2011)

(untitled) - Filippov, A. E.; Gorb, S. N. (Sci. Rep., 2016)

(untitled) - Weber, R.; Graf, T.; Berger, P.; Onuseit, V.; Wiedenmann, M.; Freitag, C.; Feuer, A. (Opt. Express, 2014)

(untitled) - Taylor, L. L.; Scott, R. E.; Qiao, J. (Opt. Mater. Express, 2018)

(untitled) - Plamadeala, C.; Hischen, F.; Friesenecker, R.; Wollhofen, R.; Jacak, J.; Buchberger, G.; Heiss, E.; Klar, T. A.; Baumgartner, W.; Heitz, J. (R. Soc. Open Sci., 2017)

(untitled) - Comanns, P.; Winands, K.; Pothen, M.; Bott, R. A.; Wagner, H.; Baumgartner, W. (Proc. SPIE, 2016)

(untitled) - Greiner, C.; Schäfer, M. (Bioinspiration Biomimetics, 2015)

(untitled) - Cuervo, P.; López, D. A.; Cano, J. P.; Sánchez, J. C.; Rudas, S.; Estupiñán, H.; Toro, A.; Abdel-Aal, H. A. (Surf. Topogr.: Metrol. Prop., 2016)

(untitled) - Liu, J. M. (Opt. Lett., 1982)

(untitled) - Finger, J.; Reininghaus, M. (Opt. Express, 2014)

(untitled) - Bauer, F.; Michalowski, A.; Kiedrowski, T.; Nolte, S. (Opt. Express, 2015)

(untitled) - Inogamov, N. A.; Zhakhovsky, V. V.; Ashitkov, S. I.; Emirov, Y. N.; Faenov, A. Y.; Pikuz, T. A.; Ishino, M.; Kando, M.; Hasegawa, N.; Nishikino, M.; Kawachi, T.; Agranat, M. B.; et al. (J. Phys.: Conf. Ser., 2014)

(untitled) - Sedao, X.; Abou Saleh, A.; Rudenko, A.; Douillard, T.; Esnouf, C.; Reynaud, S.; Maurice, C.; Pigeon, F.; Garrelie, F.; Colombier, J.-P. (ACS Photonics, 2018)

(untitled) - Florian, C.; Caballero-Lucas, F.; Fernández-Pradas, J. M.; Bosch, S.; Morenza, J. L.; Serra, P. (J. Phys. D: Appl. Phys., 2015)

(untitled) - Marmur, A. (Langmuir, 2003)

(untitled) - Kim, D.; Pugno, N. M.; Ryu, S. (Sci. Rep., 2016)

(untitled) - Kietzig, A.-M.; Hatzikiriakos, S. G.; Englezos, P. (Langmuir, 2009)

(untitled) - Weber, R.; Graf, T.; Freitag, C.; Feuer, A.; Kononenko, T.; Konov, V. I. (Opt. Express, 2017)